2017
DOI: 10.1016/j.tcs.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and complexity results on jumping finite automata

Abstract: In a jumping finite automaton, the input head can jump to an arbitrary position within the remaining input after reading and consuming a symbol. We characterize the corresponding class of languages in terms of special shuffle expressions and survey other equivalent notions from the existing literature. Moreover, we present several results concerning computational hardness and algorithms for parsing and other basic tasks concerning jumping finite automata.Proposition 10. Let M 1 , M 2 , M 3 be arbitrary languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 74 publications
(125 reference statements)
1
11
0
Order By: Relevance
“…Interestingly enough, also the problem of detecting emptiness of the intersection of only two JFA languages is NP-hard. This and a related study on ETH-based complexity can be found in [37]. For the intersection of k JFAs, the proof of Proposition 2 actually shows the analogous result also in that case.…”
Section: Jumping Finite Automatasupporting
confidence: 62%
See 4 more Smart Citations
“…Interestingly enough, also the problem of detecting emptiness of the intersection of only two JFA languages is NP-hard. This and a related study on ETH-based complexity can be found in [37]. For the intersection of k JFAs, the proof of Proposition 2 actually shows the analogous result also in that case.…”
Section: Jumping Finite Automatasupporting
confidence: 62%
“…Frankly speaking, we are only aware of the papers [29,37] on these topics. Returning to the survey of Holzer and Kutrib [7], it becomes clear that there are quite a many hard problems related to finite automata and regular expressions that have not yet been examined with respect to exact algorithms and ETH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations